Determinan Yang Berhubungan Dengan Prevalensi Anemia Pada Remaja Putri Di SMA X di Wilayah Banjarmasin - Anita Herawati; Linda Kusuma Wati; Khairatun Nisa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
One of the problems that often arise in adolescent girls is anemia. Adolescent girls have a higher risk of experiencing anemia than adolescent boys. Many factors are related to the incidence of anemia in adolescent girls. One of the causes of anemia in adolescent girls is menstruation, during which blood will continue to flow until it requires the most important nutritional intake, namely iron.To determine the determinants related to the prevalence of anemia in adolescent girls at SMA X Banjarmasin Region.This study used a cross-sectional design. The sample in this study were all adolescent girls at SMA X Banjarmasin Region with a total of 64 students. The research data were collected using a questionnaire and then analyzed using the chi square test.The majority of respondents did not experience anemia, namely 50 people (78.1%), while 14 respondents had anemia (21.9%). The results of the bivariate analysis showed that knowledge about anemia (0.010), menstrual cycle (0.000) and compliance with iron supplement tablet consumption (0.013) were related to the incidence of anemia in adolescent girls at SMA X Banjarmasin Region.Determinants related to the prevalence of anemia in female adolescents at SMA X in Banjarmasin are knowledge, menstrual cycle and compliance with iron supplement tablet consumption.